Phytotherapy for osteoarthritis - Trifunovic-König, Milena; Klose, Petra; Cramer, Holger; Koch, Anna K.; Dobos, Gustav; Langhorst, Jost (Zeitschrift für Phytotherapie, 2016)
Background: In order to present recent findings on the effectiveness and safety of phytotherapy for treatment of osteoarthritis (OA) we summarized the two latest Cochrane reviews (Cameron & Chrubasik, 2013; Cameron & Chrubasik, 2014). One of them included oral and the other topical herbal treatment options as a treatment for OA.Methods: We conducted a thorough evaluation of the Cochrane reviews. We assessed methodological quality of the reviews and extracted evidence.Results: Meta-analyses found evidence for effects of the oral herbal products Boswellia serrata and only partially for avocado-soybean unsaponifiable (ASU). However, they included only a small number of primary studies. The systematic review on topical herbal treatments included fewer trials and did not include a meta-analysis.Discussion: Based on the qualitative synthesis Boswellia serrata can be applied in the treatment of OA. It is not clear if ASU can be recommended. No valid recommendation can be given for or against other herbal therapies due to a lack of randomized clinical trials in the field.
Keywords: osteoarthritis; herbs; herbal therapy; phytotherapy; review